A method for finding a common linear divisor of the matrix polynomials over an arbitrary field - Prokip, V. M.; Khudyi, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Conditions are found for existence of a common linear unital divisor with a given characteristic polynomial of regular matrix polynomials over an arbitrary field. The result obtained is also applied to finding a common solution of matrix polynomial equations.